2018
DOI: 10.3390/s18020461
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Microfiber-Based Temperature Sensors

Abstract: Optical microfiber-based temperature sensors have been proposed for many applications in a variety of industrial uses, including biomedical, geological, automotive, and defense applications. This increasing demand for these micrometric devices is attributed to their large dynamic range, high sensitivity, fast-response, compactness and robustness. Additionally, they can perform in-situ measurements remotely and in harsh environments. This paper presents an overview of optical microfibers, with a focus on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 114 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…It has been demonstrated that the sensitivity of the tapered fiber is largely determined by its geometrical parameters, especially the taper lengths and diameters [3,15,33]. The tapered region is particularly important for sensing applications as it allows maximum interaction with the surroundings, and thus it has predictable compactness and sensitivity improvement.…”
Section: Sensor Structure and Principlementioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the sensitivity of the tapered fiber is largely determined by its geometrical parameters, especially the taper lengths and diameters [3,15,33]. The tapered region is particularly important for sensing applications as it allows maximum interaction with the surroundings, and thus it has predictable compactness and sensitivity improvement.…”
Section: Sensor Structure and Principlementioning
confidence: 99%
“…Therefore, a large variety of fiber optic temperature sensors have been envisioned and demonstrated for accurate temperature measurement. The sensitive structures include the fiber Bragg grating (FBG) [5][6][7], long period fiber grating (LPFG) [8], Fabry-Perot cavity [9][10][11], Mach-Zehnder interferometer [12][13][14], microfiber-based structures [3,15], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various types of optical fiber sensors, tapered optical microfiber sensors have continued to receive considerable attention, given their additional advantages of high sensitivity and miniature size [10]. The fabrication of a tapered optical microfiber is performed by simultaneously heating and pulling a section of an optical fiber into microscale diameter [11].…”
Section: Introductionmentioning
confidence: 99%
“…Existing polymer optical sensors mainly include the metal surface plasmon waveguide sensor [4,5,6], the Mach–Zehnder (M–Z) waveguide sensor [7,8], and the optical fiber stress sensor [9,10]. Currently, sensing temperature [11,12,13,14] and antibody antigens [15,16,17] is widespread in the organism-sensing field. Many optical sensors are capable of these functions, of which the majority are based on M–Z optical waveguide.…”
Section: Introductionmentioning
confidence: 99%